How do we think? - Ballard, Carol (Austin, Tex. : Raintree Steck-Vaughn, 1998)
Describes the various parts of the brain and the nervous system and how they function to enable us to think, feel, move, and remember.
Includes bibliographical references (p. 31) and index.
Keywords: Brain -- Juvenile literature; Nervous system -- Juvenile literature; Thought and thinking -- Juvenile literature; Brain; Nervous system